2019
DOI: 10.1016/j.msea.2019.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of second phase particles on mechanical properties and grain growth in a CoCrFeMnNi high entropy alloy

Abstract: Effect of annealing of a cold-worked CoCrFeMnNi alloy at temperatures of 500-900°C for 1-50 h on the structure and mechanical properties was studied in the present work. Annealing for an hour resulted in: i) recrystallization of the face-centered cubic (fcc) matrix at 600-900°C; ii) precipitation of a Cr-rich body-centered cubic (bcc) phase at 500-700°C or a sigma phase particles at 600-800°C. Moreover, an increase in the annealing time to 50 h at 600°C resulted in a continuous growth of both the fcc grans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(37 citation statements)
references
References 49 publications
4
32
1
Order By: Relevance
“…The nano-precipitates can effectively improve the mechanical properties of the alloy. It has been reported that precipitation of second phase particles can pin grain boundaries, suppress grain growth, and result in the formation of fine-grain microstructures in the FCC type HEAs [ 37 , 38 , 39 ]. According to Figure 1 c, the average grain size of the extruded alloy is about 20 μm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nano-precipitates can effectively improve the mechanical properties of the alloy. It has been reported that precipitation of second phase particles can pin grain boundaries, suppress grain growth, and result in the formation of fine-grain microstructures in the FCC type HEAs [ 37 , 38 , 39 ]. According to Figure 1 c, the average grain size of the extruded alloy is about 20 μm.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, the tensile strength was as high as 1.2 GPa and the ductility was about 19%. In fact, the size, content, and distribution of precipitates have been seen to have great effects on the mechanical performance of CoCrFeNi-based HEAs [ 20 , 21 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. It is known that precipitation behavior is closely related to the heat treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, when the powder metallurgy approach for the alloy preparation was applied, the ultra-fine-grained structure was reached. The precipitation of secondary phases (usually Cr rich phase) during the alloy preparation and processing was also described by some authors [1,6].…”
Section: Introductionmentioning
confidence: 92%
“…A large variety of HEAs exists, but single-phase equiatomic five-element HEA Co-Cr-Fe-Mn-Ni, the so-called Cantor alloy, is one of the most studied [5]. The single-phase solid solution high-entropy alloys have a potential for solid solution hardening and if the single-phase fcc lattice structure is reached, a large number of slip systems ensures good ductility of the material [6][7][8][9]. Nevertheless, the experimental data about mechanical behaviour of this alloy type are still not fully understood and in some cases are controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation